Algunos factores que afectan la transmisión del virus del rayado fino del maíz por Dalbulus maidis DeLong & Wolcott - González, Víctor; Gamez, Rodrigo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Previous reports have shown that the leafhopper Dalbulus maidis transmits rayado fino virus (RFV) of maize in a manner characteristic of viruses that multiply in their insect vectors. Further studies of the virus-vector relationships described in this paper showed that no difference in longevity exists between RFV-transmitters and no-transmitters. Young adults and 3rd or 4th instar nymphs were equally efficient vectors of the virus, females were more efficient vectors than males and lived longer. No transovarial transmission of RFV was observed in a progeny of 110 insects obtained from viruliferous females. The incubation period of RFV in its vectors averaged 13.5 days at 20°C, 12.5 days at 25°C, and 12 days at 30°C. However more insects were capaable of virus transmission after incubation periods at 20-25°C than those incubated at 30°C. When insects were incubated for 10 days at 25°C, subsequent tests for their ability to transmit the virus at 20, 25 or 30°C showed that the number of transmitters was always lower at 30°C and markedly higher at 20 or 25°C. Observations indicated that the duration of the nymphal and adult stages of D ma dis was 15.6 and 31.5 days, respectively, at 25±1°C